(untitled) (International Journal of Innovative Computing, 2013)
The overall interest of various routing protocols is to efficiently transmit data from source node to the destination node even in the presence of node mobility challenges. However, many routing protocols take on these challenges using different approaches. In this paper, we implement an improvement on the cluster based routing protocol using a different clustering algorithm and also using fuzzy logic to determine the best routing path across intermediate clusterheads under two clusterhead node constraints such as clusterhead node degree and hop count. We proposed an Improved Cluster Based Routing Protocol (i-CBRP) based on the implementation of fuzzy scores of each intermediate clusterhead along the routing path. This proposal was implemented in NS2 network simulator and it was evaluated alongside CBRP using the following evaluation parameters: average cluster head change rate, packet delivery capacity, end to end delay and average throughput of the network. The simulation results show that i-CBRP performs better than CBRP in all areas of performance comparison. Keywords — Mesh Clients, Wireless Networks, Clustering Algorithm, Fuzzy Logic Controller, Clusterheads.